Hubungan Asupan Energi, Karbohidrat, Lemak, Protein dan Natrium dengan Kejadian Hipertensi pada Lansia di Puskesmas Sei Langkai Kota Batam - Najwa Amalia Putri; Haqqelni Nur Rosyidah; Didi Yunaspi (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2026)
Hypertension is a non-communicable disease that is still a major health problem in Batam City. This study aims to determine the relationship between energy, carbohydrate, fat, protein, and sodium intake with the incidence of hypertension in the elderly at the Sei Langkai Public Health Center, Batam City. This type of study is observational with a cross-sectional design. A sample of 73 elderly people was selected using a purposive sampling technique based on predetermined inclusion and exclusion criteria. The results showed that the majority of elderly participants had adequate energy intake (54.8%) and carbohydrate intake (57.5%), while inadequate intake was observed for fat (56.2%), protein (52.1%), and sodium (79.5%). In addition, 54.8% of the participants were found to have hypertension. Statistical analysis revealed significant associations between energy intake (p=0.020), carbohydrate intake (p=0.004), fat intake (p=0.009), and protein intake (p=0.015) and the incidence of hypertension among the elderly. However, no significant association was found between sodium intake (p=0.300) and the incidence of hypertension among the elderly. It can be concluded that energy, carbohydrate, fat, and protein intake were significantly associated with the incidence of hypertension among the elderly, whereas sodium intake was not. The elderly are advised to implement a healthy and balanced dietary intake.